Oil Palm and Nipah Frond Silages and Their Utilization by Sheep - Abdalla, Sideig Adam (2001)
A series of experiments was conducted to study the quality of s i l ages made from oil palm (Elaeis guineesis) (OPF) and nipah fronds (Nypafi'ltficans) (NF) and to see the effects of adding molasses or urea on the silages. The results showed that fresh OPF had significantly (P< 0.05) higher dry matter (DM), ether extractives (EE) and neutral detergent fiber (NDF) than NF. The non-structural carbohydrates (NSC), ash, lignin and tanni n of OPF were significantly (P<0.05) lower than those of NF.The crude protein (CP), pH and lactic acid of the fresh OPF and NF were similar, but the buffering capacity (BC) of the fresh OPF was significantly (P<0.05) lower than NF. Anatomical investigations showed that the two types of fronds were ditTerent i n their structures. In OPF, the hypodermic l ayer consisted of two l ayers o f thin wal led cells, while i n NF the outermost layer of the hypodermis was made up 0 f thick walled cel ls. In addition, l ignified palisade cells were present below the epidermis of N F, but were absent in OPF. The pH of ensi led OPF was significantly (P<0.0 1 ) lower while the lactic acid higher than that of NF. Ensiled OPF had higher (P<O.Ol ) Be at day 30 of ensilage than that of NF. The addition of 1 0% molasses increased l actic acid content of O PF but not o f NF, while 3% urea added singly or with 1 0% molasses did not i mprove the ensilability of both OPF and NF. However, 3 0% molasses increased the lactic acid of NF fro m 1 4.2 to 5 0 .4 g/kg DM and lowered its pI-I fi-om 4.7 to 4 . 0 at day 3 0 . Digesti bility studies in situ in sheep showed that the potential degradabil ity of both untreated or molasses treated OPF were significantly (P<0 . 0 1 ) higher than that o f N F . The rumen ammonia nitrogen concentration o f sheep fed OPF silage was significantly higher than sheep fed NF silage. In the feeding trial conducted for 63 days, lambs fed m olasses treated NF silage showed significantly ( P< 0.05) higher si lage intake as wel l as l ive weight gai n (L WG) than lambs fed untreated NF silage. S imilarly, lambs jed mo lasses treated OPF silage s howed higher silage i ntake and L WG than lambs fed untreated O P F. A regression equation to show the relationship between % potential clegraclability (a + b) ancl voluntary feed intake (VFI) in g/kg W 075 was 0 . 5 (a + b) + 51.5, (r2 = 0.65).